Medical and molecular virology - Suchman, Erica, author (Colorado State University. Libraries, 2020)
This book was created for upper division microbiology students studying virology. It will describe the molecular biology and major diseases of virus families that cause significant disease in animals and humans. This book is by no means meant to be exhaustive. In fact, because virology can be so overwhelming, the author has tried to keep the book as simple as possible, while still giving the reader a solid understanding of the molecular mechanisms of viral replication and pathogenesis. This book is different than other virology textbooks in that it is laid out grouping viruses by how they replicate. This should hopefully allow you, the reader, to think about why these viruses replicate similarly, and why replication strategies may be different than those used by other viruses.
Keywords: Open educational resources